Size dependent anti-invasiveness of silver nanoparticles in lung cancer cells. Issue 37 (5th July 2019) - Que, Yu Mei; Fan, Xiao Qing; Lin, Xiao Juan; Jiang, Xiao Li; Hu, Ping Ping; Tong, Xiao Yong; Tan, Qun You
Abstract : Size-dependent anti-invasiveness effect of AgNPs was determined using A549 lung adenocarcinoma cells. The 13 nm AgNPs can significantly inhibit the migration and invasion of A549 cells and induce the elevated level of ROS and NF-κB directed cell apoptosis. Abstract : The molecular mechanism of cancer cell death caused by silver nanoparticles (AgNPs) of different sizes is investigated. Compared with the larger nanoparticles, 13 nm AgNPs significantly inhibit the migration and invasiveness of lung adenocarcinoma A549 cells, induce elevated reactive oxygen species and lead to NF-κB directed cellular apoptosis.